The Golden Middle Class Neighborhood: Trends in Residential Segregation and Consequences for Offspring Outcomes - Simen Markussen; Knut Røed (Institute of Labor Economics (IZA), 2018)
Based on Norwegian administrative registers we provide new empirical evidence on the effects of the childhood neighborhood's socioeconomic status on educational and labor market performance. A neighborhood's status is measured annually by its prime age inhabitants' earnings ranks within larger commuting zones, and the childhood neighborhood status is the average status of the neighborhoods inhabited from birth to age 15. Identification of causal effects relies on within-family comparisons. Our results reveal a hump-shaped relationship between the socioeconomic status of the childhood neighborhood and school results at age 15-16, such that the optimal neighborhood is of medium rank. The top-ranked neighbor-hoods are as bad as the bottom-ranked. Similar results are obtained for educational and labor market outcomes measured at higher ages.
Keywords: C21; I24; R23; Z13; 330; segregation; neighborhood effects; social mobility; educational outcomes